2022
DOI: 10.3390/ani12233317
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Decadal (2012–2021) Dynamics of Spatial Ichthyoplankton Distribution in Sevastopol Bay (Black Sea) Affected by Hydrometeorological Factors

Abstract: High mortality of fish in the early stages of ontogenesis requires the detection of factors affecting it and is an extremely important problem. For this reason, we tried to consider the influence of some hydrometeorological factors on the intra-decadal dynamics and spatial distribution of ichthyoplankton abundance in Sevastopol Bay. To this end, we analyzed ichthyoplankton samples collected in 2012–2021 in Sevastopol Bay, and the four districts were identified. The ichthyoplankton distribution by areas was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that the exposure of fish to pollutants can lead to endocrine disruption, which can have toxic effects through their interference with the normal functioning of the endocrine system, which is responsible for regulating various physiological processes in the body. These disruptors can mimic or block the actions of natural hormones, leading to a range of negative effects such as interferences in reproduction, changes in behavior, immune system suppression, developmental abnormalities and interference with metabolism [10][11][12][13][14][15]. Anthropogenic sources of PAHs and POPs include: Industrial processes: the manufacture of chemicals, and oil and gas extraction [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the exposure of fish to pollutants can lead to endocrine disruption, which can have toxic effects through their interference with the normal functioning of the endocrine system, which is responsible for regulating various physiological processes in the body. These disruptors can mimic or block the actions of natural hormones, leading to a range of negative effects such as interferences in reproduction, changes in behavior, immune system suppression, developmental abnormalities and interference with metabolism [10][11][12][13][14][15]. Anthropogenic sources of PAHs and POPs include: Industrial processes: the manufacture of chemicals, and oil and gas extraction [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, these characteristics have led to clusters of specialized industries [ 3 , 4 ], as well as an increase in the coastal population and urbanization [ 5 ], originating environmental impacts. Furthermore, coastal areas and oceans receive direct discharges of wastewater, runoff, and inland waters, serving as final sinks for global pollution [ 6 , 7 , 8 , 9 ]. This results in the deterioration of the water quality [ 10 , 11 ] and the accumulation of contaminants, such as trace metals [ 12 , 13 , 14 ], pesticides [ 15 , 16 ], hydrocarbons [ 17 ], and persistent organic pollutants [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, work under environmentally realistic conditions considers the interactions that occur between the chemicals in the effluent and the complexity of the receiving environment [4]. Recent studies have shown that hematological parameters are often used as valuable indicators for assessing fish health, and that the use of pelagic fish data allows for comprehensive monitoring studies of effluents [5,6]. The effects of wastewater treatment plant effluents on biological neurotoxicity, cytotoxicity, genotoxicity and estrogenic effects have been reported in recent decades [7].…”
Section: Introductionmentioning
confidence: 99%